2017
DOI: 10.1186/s13046-017-0627-9
|View full text |Cite
|
Sign up to set email alerts
|

CLDN6 promotes chemoresistance through GSTP1 in human breast cancer

Abstract: BackgroundClaudin-6 (CLDN6), a member of CLDN family and a key component of tight junction, has been reported to function as a tumor suppressor in breast cancer. However, whether CLDN6 plays any role in breast cancer chemoresistance remains unclear. In this study, we investigated the role of CLDN6 in the acquisition of chemoresistance in breast cancer cells.MethodsWe manipulated the expression of CLDN6 in MCF-7 and MCF-7/MDR cells with lv-CLDN6 and CLDN6-shRNA and investigated whether CLDN6 manipulation lead t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 39 publications
3
36
0
1
Order By: Relevance
“…Recently, the significance of GSTP1 for evaluating sensitivity to anticancer drugs such as CDDP, 5‐FU, doxorubicin, and other types of drug, has been described. The relationship between GSTP1 expression and resistance to CDDP was especially demonstrated in lung cancer, breast cancer, ovarian cancer, and osteosarcoma in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, the significance of GSTP1 for evaluating sensitivity to anticancer drugs such as CDDP, 5‐FU, doxorubicin, and other types of drug, has been described. The relationship between GSTP1 expression and resistance to CDDP was especially demonstrated in lung cancer, breast cancer, ovarian cancer, and osteosarcoma in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have found that GSTP1 is involved in resistance to CDDP in vitro or in clinical studies of EC and gastric cancer patients . Regarding 5‐FU, some reports have also shown the relationship between GSTP1 expression and drug resistance . GSTP1 affects cellular signaling by binding to important signaling proteins, which may cause malignant potential, poor prognosis and drug resistance in patients with EC, lung cancer, breast cancer, colon cancer, and prostate cancer …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Експресія GSTP пов'язана з хіміорезистентністю у клітинах лінії раку молочної залози MCF-7 (Yang et al, 2017).…”
unclassified